PENGARUH KUALITAS INFORMASI PELAPORAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP REPUTASI PERUSAHAAN (Studi Empiris Perusahaan yang Termasuk dalam Indeks LQ45 Bursa Efek Indonesia pada Tahun 2015-2019) - Dian Kristi; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of the quality of CSR reporting information (content and management system) on the reputation of companies in Indonesia. This study refers to research conducted by Pérez and Lopez-Gutierrez, (2017). The quality of CSR reporting information on the dimensions of content and management systems is considered to have a positive influence on the company’s reputation according to the hypothesis based on legitimacy theory. This research uses multiple regression analysis and classical assumption test to fulfill multiple regression test.This study finds that the quality of CSR reporting information explains the variation in the reputation of the Indonesian Stock Exchange LQ45 index companies. The results of the study explain that the quality of CSR reporting information and the quality of information from the management system reported in the CSR report has a positive effect on the company’s reputation. However, the information quality of the content reported in the CSR report has a significant negative effect on the company’s reputation.